AB0450 Outpatients' Biologic Agent Therapy in Private Practices in Western Germany – a Survey and a Retrospective Study. (9th June 2015) - Schmitz-Bortz, E.; Baraliakos, X.; Braun, J.; Arndt, S.; Christoph, J.; Dybowski, F.; Hein, L.; Hübner, G.; Igelmann, M.; Kalthoff, L.; Klinik, C.; Menne, J.; et al.
Abstract : Background: The use of biologic agents has changed treatment paradigms of rheumatic diseases in the past decade. However, the optimal strategy and dosing with this therapy is still not really clear. For example, many biologic agents have not adapted the dosage to the body weight of patients. Furthermore, it is well known that patients in clinical trials and in daily practice may differ substantially. Finally, medication costs is quite an issue in this part of Germany. Objectives: To provide real life data including costs of treatment with biologic agents in rheumatology private practices in Westfalia. Methods: A total of 13 rheumatologists in Westfalia participated in this retrospective study in 2012 and 2013. Thus, anonymized pooled data of 10.704 patients were analysed with focus on the expenses for medication in general and for biologics. In a second approach Data were extracted from a software tool (RheumaDok). Thus, the annual number of patients treated for inflammatory rheumatic diseases, their diagnosis and biologic agent therapy could be determined. Complete data of 8345 patients could be analysed. Costs were calculated from standard dosing based on the summary of product characteristics (SPC). Results: In total, 3083 patients (36.94%) with sero+ and 1958 (23.46%) with sero- rheumatoid arthritis (RA), together 5041 patients (60.41%) with RA were identified, while 778 patients (9.32%) had psoriatic arthritis (PsA) and 956 (11.46%) axial spondyloarthritis (axSpA). Another 1570 (18.81%) had other rheumatic diseases and were excluded from the study. The biologic agent ratio was 7.9% (range 5.5 to 8.7%). Disease specific ratios on RA, PsoA and axSpA are shown in Fig.1 . with axSpA as the largest fraction. The overall budget of 11 rheumatologists was 14.3 Mio € per year for all drugs. Of these, 10.47 Mio € (74.37%) were spent for 733 patients (6.85%) on biologics. This reveals annual costs of 14.286 € per patient on biologics, a rate of 65-68% compared to that expected for Etanercept (ETA) or Adalimunab (ADA) by their SPC. Out of allbiological agents employed, the proportion of ETA was 35.1%, of ADA 29.4%, Infliximab 12.3% and others 23.2%. Conclusions: The fact that the largest proportion of patients treated with biologics had a diagnosis of axSpA is surprising and deserves further study. The most likely explanation is that rheumatologists take care much more frequently for mild to moderate RA than for axSpA patients. ETA and ADA are the most sold biologics in Germany, this was confirmed for Westfalia. Compared to the official price lists, biologic agents were on average prescribed in a reduced schedule of about 2/3 of the standard dosing. In 2013, the ratio of RA patients on biologic agents was only 6.7%. This is a considerably low figure compared to data of the German core set documentation (25%) 1 . References: S. Bischoff et al. (2012) Kerndokumentation, http://dgrh.de/fileadmin/media/Forschung/Versorgungsforschung/ErwachsenenKerndok/standardpraesentation_2012_dgrh_extern.pdf Acknowledgements: Partially sponsored by an unrestricted grant by Pfizer Disclosure of Interest: None declared